Seroprevalence of Cysticercosis in Children and Young Adults Living in a Helminth Endemic Community in Leyte, the Philippines - Jin-Mei Xu; Luz P. Acosta; Min Hou; Daria L. Manalo; Mario Jiz; Blanca Jarilla; Archie O. Pablo; Remigio M. Ovleda; Gretchen Langdon; Stephen T. McGarvey; Jonathan D. Kurtis; Jennifer F. Friedman; et al. (Journal of Tropical Medicine)
Cysticercosis is a significant public health problem in countries where pigs are raised for consumption and remains an important cause of neurological disease worldwide. The Philippines is considered an endemic area for cysticercosis because cases in both humans and pigs have been reported; however, epidemiologic information stays limited. We conducted a pilot survey of the seroprevalence of human cysticercosis in a village in Leyte, the Philippines, by measuring antibody specific for Taenia solium cyst-fluid antigen. There were 497 subjects aged 7–30 years in our study and most subjects were infected with one or more helminths. The overall cysticercosis seroprevalence in this population was 24.6% (95% CI: 20.82% ~ 28.58%) with no significant difference based on age, sex, or other helminth coinfection status. Although the sample may not be representative of the whole community, the findings suggest that cysticercosis is a significant, but underrecognized public health concern in the Philippines.